The Association of Cell-Free LncH19 and miR-29b Expression with the PI3K/AKT/HIF-1/VEGF Pathway in Patients with Diabetic Nephropathy: In Silico Prediction and Clinical Validation - Noha M. Abd El-Fadeal; Basma Osman Sultan; Asmaa K. K. AbdelMaogood; Essam Al Ageeli; Fatma Tohamy Mekhamer; Sherihan Rohayem; Ahmed Shahidy; Nora Hosny; Manal S. Fawzy; Mohammed M. Ismail; Hidi A. A. Abdellatif (Current Issues in Molecular Biology)
Diabetic nephropathy (DN) affects about one-third of patients with diabetes and can lead to end-stage renal disease despite numerous trials aimed at improving diabetic management. Non-coding RNAs (ncRNAs) represent a new frontier in DN research, as increasing evidence suggests their involvement in the occurrence and progression of DN. A growing body of evidence suggests that long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) in DN signaling pathways might serve as novel biomarkers or therapeutic targets, although this remains to be fully explored. Our study included four groups, each comprising 40 adults: patients with diabetes (a) without albuminuria, (b) with microalbuminuria, (c) with macroalbuminuria, and a control group. All participants underwent history-taking and clinicolaboratory assessments, including CBC, fasting blood sugar, HbA1c, lipid profile, liver function, and renal function tests. Additionally, expressions of lncRNA H19, miRNA-29b, PI3K, AKT, mTOR, and HIF-1 alpha were assessed using qPCR. lncRNA H19 expression was upregulated in patients with albuminuria compared to the DM group. Furthermore, based on qPCR, the level of lncRNA H19 was negatively correlated with eGFR and miRNA-29b expression. On the other hand, the lncRNA H19 level was positively correlated with PI3K, AKT, mTOR, and HIF-1 alpha levels. We also found that the lncH19/miRNA-29b ratio was significantly increased in patients with DN and macroalbuminuria. In conclusion, lncRNA H19 was upregulated in patients with DN, and this increase was associated with miRNA29b downregulation. Therefore, our study suggests a novel link between the lncH19/miRNA-29b ratio and DN, indicating that it might serve as a potential biomarker for the dynamic monitoring of DN.